2000
DOI: 10.1136/gut.46.6.782
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of cyclooxygenase 1 and cyclooxygenase 2 in Helicobacter pylori related gastritis and gastric ulcer tissues in humans

Abstract: Background-Prostaglandin endoperoxide synthase/cyclooxygenase (COX) is the key enzyme in gastric mucosal protection and repair but its cellular localisation in the human stomach is still unclear. Aims-To investigate immunohistochemically the cellular distribution of COX-1 and COX-2 proteins in the human stomach with or without gastritis or ulceration. Patients and methods-Tissues were obtained by surgical resection of gastric ulcers associated with perforation (n=9) or by biopsy from Helicobacter pylori positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
89
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 33 publications
9
89
0
1
Order By: Relevance
“…We and others have shown that H. pylori increases COX-2 expression in human gastric mucosa (14,15) and in gastric epithelial cell lines (21,25). H. pylori is strongly linked to gastric cancer (26), and the chronic inflammation associated with the longstanding infection is presumed to be the main cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that H. pylori increases COX-2 expression in human gastric mucosa (14,15) and in gastric epithelial cell lines (21,25). H. pylori is strongly linked to gastric cancer (26), and the chronic inflammation associated with the longstanding infection is presumed to be the main cause.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that the inducible form of cyclooxygenase, (COX) 4 -2, is up-regulated in human H. pylori gastritis tissues and localizes to lamina propria mononuclear cells (14,15). Increased levels of PGE 2 have also been demonstrated in the infected gastric mucosa (16).…”
mentioning
confidence: 96%
“…On the other hand, COX-2 is an inducible gene, originally found to be up-regulated by inflammation or other stimuli such as mitogens, cytokines, various growth factors, and tumor promoters (10 -12). COX-2 was shown to be activated in inflammatory cells, vascular endothelial cells, and fibroblasts (13), as well as macrophages (14). High levels of COX-2 have also been reported in a variety of cancer types, including esophageal carcinoma (15).…”
mentioning
confidence: 99%
“…In the normal stomach of humans and animals, most studies found COX-2 mRNA and protein to be expressed at low or undetectable levels, and the physiological role of COX-2 in normal stomach remains to be defined (Kargman et al 1996;Ristimaki et al 1997;Zimmermann et al 1998;Jackson et al 2000;Sung et al 2000). However, COX-2 overexpression has been reported in several different pathological gastric conditions, including ulcer healing (Mizuno et al 1997;Ristimaki et al 1997;Kishimoto et al 1998;Sawaoka et al 1998;Shigeta et al 1998;Fu et al 1999;McCarthy et al 1999;Jackson et al 2000;Sung et al 2000;Tatsuguchi et al 2000). In the latter, induced COX-2 expression was detected at the ulcer margins or in the ulcer bed by immunohistochemistry in gastric ulcers in humans and in experimentally induced gastric ulcers in rats and mice (Mizuno et al 1997;Shigeta et al 1998;Jackson et al 2000;Tatsuguchi et al 2000).…”
mentioning
confidence: 99%